Pengaruh Return On Assets (ROA) Return On Equity (ROE), Net Profit Margin (NPM) Dan Earning Per Share (EPS) Terhadap Harga Saham (Studi Pada Sektor Jasa Kontruksi Terdaftar Di Bursa Efek Indonesia Periode 2014-2018) - Andrew Ralphon Manullang (Universitas Batanghari Jambi, 2019)
The purpose of this study is 1). To determine the effect of the Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) ratios simultaneously to the stock price. 2). To determine the effect of the Return on Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) partially to the stock price. The data used in this research is library research, in the form of documentation sourced from the IDX website in the form of financial statements of construction companies. The conclusion of this study is 1). Simultaneously the four variables ROA, ROE, NPM and EPS have an influence on the Stock Price. This is evidenced from Fcount of 12.920 greater than F table which is equal to 2.80 with 5% (12,920> 2.80). Based on the determination coefficient (R2) the R Square value that is equal to 0,721. This means that ROA, ROE, NPM and EPS together have an effect of 0.721 x100% = 72,1%. While the remaining 27.9% is influenced by other factors not involved in the study. 2). Partially ROE do not have an influence on Stock Prices, this is evidenced from the value of t calculated ROE ratio of -1.379 smaller than t table of 2,085. (-1.379 <2,085). While the ROA, NPM and EPS have an influence on Stock Prices, but in the NPM variable the effect that is given to the stock price is precisely towards the negative. This is known from t count NPM negative value of -4,067 while t count ROA and EPS positive value 2,323 and 6.807 and greater than t table that is equal to 2,085 (2,323 and 6.262> 2,085)